Exogenously applied dsRNA molecules deriving from the Zucchini yellow mosaic virus (ZYMV) genome move systemically and protect cucurbits against ZYMV. (31st July 2017) - Kaldis, Athanasios; Berbati, Margarita; Melita, Ourania; Reppa, Chrysavgi; Holeva, Maria; Otten, Patricia; Voloudakis, Andreas
Summary: Zucchini yellow mosaic virus (ZYMV) causes serious damage in a large number of cucurbits, and control measures are necessary. Transgenic cucurbits expressing parts of the ZYMV genome have been shown to be resistant to the cognate virus. A non‐transgenic approach involving the exogenous application of double‐stranded RNA (dsRNA) has also been shown to induce resistance in tobacco against Cucumber mosaic virus (CMV) and Tobacco mosaic virus (TMV). In the present study, dsRNA molecules derived from the helper component‐proteinase (HC‐Pro) and coat protein (CP) genes of the ZYMV_DE_2014 isolate were produced in vitro . On exogenous dsRNA application in cucumber, watermelon and squash plants, dsRNA HC‐Pro conferred resistance of 82%, 50% and 18%, and dsRNA CP molecules of 70%, 43% and 16%, respectively. On deep sequencing analysis of ZYMV‐infected watermelon, hot‐spot regions for viral small interfering RNAs (vsiRNAs) in the genome of ZYMV were identified. Stem‐loop reverse transcription‐polymerase chain reaction (RT‐PCR) detection of selected 21‐nucleotide‐long vsiRNAs in plants that received only dsRNA molecules suggested that the dsRNAs exogenously applied onto plants were successfully diced, thus initiating RNA silencing. dsRNA molecules were found to be progressively degraded in planta, and strongly detected by semi‐quantitative RT‐PCR for at least 9 days after exogenous application. Moreover, dsRNA molecules were detected in systemic tissue of watermelon and squash, showing that dsRNA is transported long distances in these plants.